Esophageal schwannoma mimicking non-functional parathyroid adenoma on 99mTc-sestamibi imaging: a case report - Fiore, Roberto; Gombert, Edwige; La Rosa, Stefano; Dunet, Vincent; Sykiotis, Gerasimos P.; Gorostidi, François (Frontiers in Endocrinology, 2024)
Technetium-99m sestamibi single-photon emission computed tomography/computed tomography (99mTc-sestamibi SPECT/CT) is a mainstay of the pre-operative localization of parathyroid lesions. We report here the case of a 30 year-old woman with a fortuitously discovered 2 cm cervical mass for which a parathyroid origin was originally suspected due to its retro-thyroidal localization and a personal history of nephrolithiasis. Normal serum calcium and parathyroid hormone (PTH) levels excluded primary hyperparathyroidism, raising suspicion of a non-functional parathyroid adenoma, and SPECT/CT imaging showed that the mass was 99mTc-sestamibi-avid. Fine-needle aspiration (FNA) was performed; cytology was non-diagnostic but the needle washout was negative for thyroglobulin, calcitonin and PTH, arguing against a thyroidal or parathyroidal origin of the mass. Core needle biopsy revealed a schwannoma, ostensibly originating from the recurrent laryngeal nerve; upon surgical resection, it was finally found to arise from the esophageal submucosa. This case illustrates the fact that endocrinologists, radiologists, nuclear medicine, head and neck, and other specialists investigating patients with cervical masses should be aware that schwannomas need to be considered in the differential diagnosis of focal 99mTc-sestamibi uptake in the neck region.